Diagnosis Tingkat Penyakit Kulit (Acne Vulgaris) Menggunakan Metode Dempster Shafer - Raja Fuad (CV. Hawari, 2022)
Acne vulgaris is a facial skin disease that often appears in adolescents and adults. This disease can reduce the patient's self-confidence, and can cause permanent scars on the face if left unchecked. This problem can be handled with early detection, namely by building a Decision Support System (DSS) application that can diagnose the severity of acne vulgaris using the Dempster Shafer Theory (DST) method. The results of the study are in the form of an DSS application that can be used to diagnose the severity of acne vulgaris, namely by calculating and taking the diagnostic results that have the highest density value.